Analisis Kualitas Aplikasi E-Exam Menggunakan Standar ISO 25010 - Gugi Tyas; Detty Purnamasari; Amat Suroso (Politeknik Harapan Bersama, 2021)
Examination is a process carried out to measure the achievement of student competencies on an ongoing basis in the learning process, to monitor progress, make learning improvements, and determine student learning success. In 2019, SMK Negeri 6 Bekasi City began to use the E-Exam Application for the implementation of exams, both the Mid-Semester Examination or better known as UTS, Semester Final Examination or better known as UAS and School Examination or better known as US. Approaching 2 years of use, the E-Exam Application of SMK Negeri 6 Bekasi City has not been analyzed for software. The results of the evaluation of the quality of the E-Exam software at SMK Negeri 6 Bekasi City are expected to be a reference for developing and fulfilling the wishes of every citizen of SMK Negeri 6 Bekasi City, to be able to carry out online exams well. ISO 25010 testing is a standard that is widely used to evaluate, measure and test the quality of software. The ISO used for this research is version 25010, this version is a continuation of ISO/IEC 9126 with the addition of several structures and parts of the quality model standard. In this study, we will discuss the analysis of application quality using the ISO 25010 standard.